Teachers' Understanding and Application of Algebra Learning at the Kindergarten in Group B - Astuti, Febru Puji (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Early childhood education institutions are expected to provide optimal opportunities forchildren to access mathematical ideas and concepts include algebra. Existing researchshows the challenges in learning mathematics for children, especially algebra, one of whichis the competence of educators related to mastery skills and knowledge of the material inteaching. This research uses a survey research type by using a questionnaire as a datacollection tool. Questionnaires are used to obtain data related to a brief description of theunderstanding and application of teacher algebra learning at the Kindergarten level groupB. The findings from a sample of 33 respondents reported; 1) educators' self-understandingabout algebra learning, 42% of respondents are still not sure what algebraic materialcoverage needs to be taught, 39% of respondents stated that they know the scope ofalgebraic material that needs to be taught. 2) Teachers' teaching skills and abilities, 45%of respondents are able and frequently teach algebra material even though the practicedoes not cover all materials.